The Νόσος of Declaring that Gods do not Exist in Plato’s Laws. Isolated Cases or Groups of Ἄθεοι? - Soneira Martínez, Ramón (ARYS. Antigüedad: Religiones y Sociedades, 2020)
Denying the existence of God or gods is a common modern phenomenon in different places and religious contexts. This paper explores the possibility of its applicability in antiquity. The last decades have witnessed considerable growth in the study of atheism in antiquity. Analysis of atheistic positions in ancient societies, especially in Classical Athens, has foregrounded new development in the study of unbelief. The term “unbelief ” has been defined as a broad category to study the diverse irreligious positions not merely as the opposite of religion but as part of the religious field. This conceptualisation allows us to understand religion and unbelief as two intermingled phenomena. In recent studies on Plato’s Laws, scholars have identified atheistic groups within Athenian society. This paper aims to apply recent analytical frameworks on religious “individuation” in ancient religions to understand the role of unbelief in religious individualisation in Athens during the last decades of the 5th cent. and the first half of the 4th cent. BCE.